When The Wind Blows: Assessing The Impact of Extreme Weather on West Java Rural Bank’s Credit Risk - Tiara Zanatunnisa; Muhamad Andri Arif Pramanda; Pretisila Kartika Putri; Tiara Pradani (Jurnal Ilmiah Akuntansi, 2026)
This paper examines how extreme weather events as proxies for natural disasters affect the credit risk of rural banks (BPRs) in West Java, Indonesia, from 2022 to 2024. The scope of our study is to investigate how geographically specific environmental shocks have a bearing over rural bank credit risk. We use panel data on 212 rural banks and apply pooled ordinary least squares (POLS) regression with robust standard errors. This study combines both ROA and CAR as the bank-level variables and regional macroeconomic factors such as per capita GRDP. The results indicate that the extreme of climate fluctuations have a negative effect on Non-Performing Loans, and it is also found to be statistically insignificant, whereas flood events reveal to trigger positive and significant coefficient relationship, indicating that floods directly worsen loan quality, leading into raising banking credit risk. These findings underline the need to differentiate between chronic climatic variability and acute disaster shocks in measuring credit risk, informing climate–finance interlinkages literature with an emphasis on the sensitivity of localized rural banks to natural hazards, for which adaptive credit risk management and climate resilience strategies are needed in financial systems.